DESKRIPSI POLA PENGOPERASIAN DAN PENGGUNAAN ANGKUTAN UMUM INFORMAL DI KOTA PASIR PENGARAIAN - Khairul Fahmi (Jurnal APTEK, 2012)
Limited access to formal public transport services in several new cities greatly affect the pattern of urban transport. The other side needs of public transport services is increasing as a result of high rates of urbanization and population increase in the number of activities. These conditions encourage the emergence of alternative public transport as a filler network services that are not accessable by formal public transport that is informal public transpor informal such as beca motors, Ojek, Bajaj and others.This paper aims to provide an overview of the phenomenon of informal use of public transport (beca motor) in Pasir Pengaraian by examining the operating characteristics and service use patterns as well as informal public transport in urban areas. The review and analysis based on literature studies and actual conditions and the tendency of the use of informal public transport.